Are Australian Mental Health Services Ready for Therapeutic Virtual Reality? An Investigation of Knowledge, Attitudes, Implementation Barriers and Enablers - Chung, Olivia S.; Johnson, Alisha M.; Dowling, Nathan L.; Robinson, Tracy; Ng, Chee H.; Yücel, Murat; Segrave, Rebecca A. (Frontiers in Psychiatry, 2022)
Therapeutic virtual reality (VR) has the potential to address the challenges of equitable delivery of evidence-based psychological treatment. However, little is known about therapeutic VR regarding the perspectives and needs of real-world service providers. This exploratory study aimed to assess the acceptability, appropriateness, and feasibility of therapeutic VR among clinicians, managers and service staff working in mental healthcare and explore potential implementation barriers and enablers. Eighty-one staff from a network of private psychiatric hospitals in Victoria, Australia (aged M + SD: 41.88 + 12.01 years, 71.6% female; 64% clinical staff) completed an online survey, which included the Acceptability of Intervention Measure (AIM), Appropriateness of Intervention Measure (IAM) and Feasibility of Intervention Measure (FIM). While 91% of participants had heard about VR technology, only 40% of participants had heard of therapeutic VR being used in mental healthcare, and none had used therapeutic VR in a clinical setting. Most participants perceived VR to be acceptable (84%), appropriate (69%) and feasible (59%) to implement within their role or service and envisioned a range of possible applications. However, participants expressed concerns regarding safety, efficacy, and logistical challenges across clinical settings. Findings suggest a strong interest for therapeutic VR among Australian mental health providers working in the private system. However, dissemination efforts should focus on addressing identified barriers to ensure mental health providers are adequately informed and empowered to make implementation decisions.